ISLAM JAWA DAN RITUAL SLAMETAN DALAM PERSPEKTIF ANTROPOLOGI - Nurul Qolbi Kurniaawati (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2021)
Java is a culture that has the power of existence in midst of the arrival of various new cultures and religions. The arrival of a new religion in Java did not eliminate Javanese culture and traditions. Islam have a dialectic with Javanese culture so that it forms a distinctive and unique variant of Islam. The slametan ritual is one of the dialectical forms between the Javanese tradition and the elements of Islamic values. This study will examine the characteristics of Javanese Islam, namely the slametan ritual from an anthropological perspective. The data sources used by the researchers were obtained from several theoretical literature books and related research journals that studied Javanese rituals and Islam. The data collection method in this study is a literature study, meaning that the researcher collects some data through several text data sources which are then processed descriptively. This research will answer the question: how is Javanese Islam and the slametan ritual an anthropological perspective?